A cost-effective method to immobilize hydrated soft-tissue samples for atomic force microscopy. (October 2016) - Sahai, Suchit; Wilkerson, Marysuna; Zaske, Ana Maria; Olson, Scott D.; Cox, Charles S.; Triolo, Fabio
Immobilizing hydrated soft tissue specimens for atomic force microscopy (AFM) is a challenge. Here, we describe a simple and very cost-effective immobilization method, based on the use of transglutaminase in an aqueous environment, and successfully apply it to AFM characterization of human native Wharton's Jelly (nWJ), the gelatinous connective tissue matrix of the umbilical cord. A side-by-side comparison with a widely used polyphenolic protein-based tissue adhesive (Corning Cell-Tak), which is known to bind strongly to virtually all inorganic and organic surfaces in aqueous environments, shows that both adhesives successfully immobilize nWJ in its physological hydrated state. The cost of transglutaminase, however, is over 3000-fold lower than that of Cell-Tak, making it a very attractive method for immobilizing soft tissues for AFM characterization.